The synthesis of novel water-soluble zinc (II) phthalocyanine based photosensitizers and exploring of photodynamic therapy activities on the PC3 cancer cell line - Kocaaga, Nagihan; Turkkol, Aysegul; Bilgin, Mehmet Dincer; Erdogmus, Ali (SPRINGERNATURE, 2023)
In this study, Schiff base substituted phthalocyanine complexes (Zn1c, Zn2c) and their quaternized derivatives (Q-Zn1c, Q-Zn2c) were synthesized for the first time. Their structures have been characterized by FT-IR, H-1-NMR, UV-Vis, mass spectrometry and elemental analysis as well as. The photophysicochemical properties (fluorescence, singlet oxygen and photodegradation quantum yield) of these novel complexes were investigated in dimethylsulfoxide (DMSO) for both non-ionic and quaternized cationic phthalocyanine complexes and in aqueous solution for quaternized cationic phthalocyanine complexes. Water soluble cationic phthalocyanine compounds gave good singlet oxygen quantum yield (0.65 for Q-Zn1c, 0.66 for Q-Zn2c in DMSO; 0.65 for Q-Zn2c in aqueous solution). The binding of Q-Zn1c and Q-Zn2c to BSA/DNA was studied by using UV-Vis and fluorescence spectroscopy and these. Studies indicate that the mechanism of BSA quenching by quaternized zinc(II) phthalocyanines was static quenching. Quaternized zinc(II) phthalocyanines interacted with ct-DNA by intercalation. Quaternized zinc(II) phthalocyanines caused a decrease in cell viability and triggered apoptotic cell death after PDT was applied at a concentration that did not have a toxic effect on their own. Q-Zn1c and Q-Zn2c mediated PDT reduced the activity of SOD, CAT, GSH while increased MDA level in the prostate cancer cells. Furthermore, expression of apoptotic proteins after PDT was examined. The results revealed that the synthesized water soluble quaternized zinc(II) phthalocyanine complexes (Q-Zn1c and Q-Zn2c) are promising potential photosensitizers for PDT.
Keywords: Schiff base; Zinc(II) phthalocyanine; DNA; BSA binding; Photodynamic therapy; Prostate cancer cell line; BOVINE SERUM-ALBUMIN; SCHIFF-BASE; DNA-BINDING; PHOTOPHYSICOCHEMICAL PROPERTIES; SUBSTITUENTS; EXPRESSION; APOPTOSIS; CLEAVAGE; COMPLEX; DESIGN; Biochemistry & Molecular Biology; Biophysics; Chemistry